2019
DOI: 10.1016/j.aquatox.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and reduced salinity exacerbate the effects of oil exposure on sheepshead minnow (Cyprinodon variegatus) reproduction

Abstract: Estuaries of the northern Gulf of Mexico are dynamic environments, with fluctuations in salinity and dissolved oxygen, including areas of seasonal hypoxia. Fish that reside and reproduce in these estuaries, including sheepshead minnow (Cyprinodon variegatus; SHM), were at significant risk of oil exposure following the Deepwater Horizon oil spill. It is poorly understood how differences in environmental conditions during oil exposure impact its toxicity. The present study investigated the effects of crude oil h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Salinity is an inherent physicochemical property of seawater, and fluctuations in salinity can affect the growth, reproduction, feeding, endocrine, and metabolism of marine organisms [ 1 , 2 , 3 , 4 , 5 ]. Most marine fish are always immersed in seawater, and their behavior and internal physiological states are particularly sensitive to environmental salinity changes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salinity is an inherent physicochemical property of seawater, and fluctuations in salinity can affect the growth, reproduction, feeding, endocrine, and metabolism of marine organisms [ 1 , 2 , 3 , 4 , 5 ]. Most marine fish are always immersed in seawater, and their behavior and internal physiological states are particularly sensitive to environmental salinity changes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that co-exposure to oil and hypoxia impacts developing C. variegatus as well as Fundulus grandis [14][15][16][17] and can reduce egg production and fertilization in adults 18 . Despite the fact that both oil and hypoxia are known to affect developing C. variegatus, and that both stressors are known to affect fish immune systems, little is known about how these two stressors interact to impact immune system development.…”
mentioning
confidence: 99%
“…Carr et al (2018) suggested that exposure to oil and dispersants may therefore adversely affect testicular function in these fish. Experimental exposure of sheepshead minnows to HEWAF under different oxygen and salinity conditions demonstrated that HEWAF exposure significantly lowered egg production and egg fertilization rate, but only under hypoxic and hypoxic with low salinity scenarios, suggesting that environmental conditions might directly modulate reproductive toxicity of oil exposure in fish (Jasperse et al 2019a).…”
Section: Reproductive Capacitymentioning
confidence: 99%